Functionalization and isoreticulation in a series of metal-organic frameworks derived from pyridinecarboxylates - Pachfule, Pradip; Garai, Bikash; Banerjee, Rahul (Inorganic Chemistry, 2016)
The partially fluorinated metal-organic frameworks (F-MOFs) have been constructed from 3-fltoro-4-pyridinecarboxylic acid and trans-3-fluoro-4-pyridineacrylic acid linkers using Mn2+, Co2+, and, Cd2+ metals via the solvothetrnal method, which show isostructural isomerism with their nonfluorinated counterparts synthesized using 4-pyridinecarboxylic acid and trans-4-pyridineacrylic acid, respectively. The simultaneous effect of partial fluorination and isoreticulation on structure and H-2 adsorption has been studied systematically in isostructural nonfluorinated and partially fluorinated MOFs, which shows that the increment in the hydrogen uptake properties in F-MOFs is not a universal phenomenon but is rather system-specific and changes from one system to another.